An Analysis of Code-Switching on The Utterances of Agnes Mo on Daniel Mananta Network's Youtube Channel - Park Jin Ryeo; Andri Wicaksono; Dwi Rahmawati; Novi Yani; Lusi Purnama Sari (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2023)
This research aimed to analyze the phenomena of Code-Switching which examines the types and reasons for using code-switching used Agnes Monica on Daniel Mananta Network's YouTube channel entitled